Profiles of musculoskeletal development in limbs of college Olympic weightlifters and wrestlers - Kanehisa, H.; Fukunaga, T. (European Journal of Applied Physiology, 1999)
To investigate the event-related profiles of musculoskeletal development in weight-categorized athletes, we measured the cross-sectional areas (CSA) of bone and muscle in the forearm, upper arm, lower leg and thigh, using a B-mode ultrasound apparatus, in college Olympic weightlifters (OWL, n = 19) and wrestlers (WR, n = 17) and untrained men (UM, n = 24), whose body masses were within the range from 55 kg to 78 kg. Both bone and muscle CSA at all sites were significantly correlated to the two-thirds power of fat-free mass (FFM(2/3)) with correlation coefficients of 0.430-40.741 (P < 0.05) and 0.608-0.718 (P < 0.05), respectively. Moreover, there were significant correlations between bone and muscle CSA at all sites (r = 0.664-0.829, P < 0.05). Even when bone and muscle CSA were expressed relative value to FFM(2/3), both OWL and WR showed significantly greater values than UM at all sites except for the lower leg. Furthermore, the comparison of the lean (bone + muscle) CSA ratio from site to site indicated a higher distribution of lean tissues in the upper extremities in OWL and WR compared to UM. While there was no significant difference between the two athlete groups in FFM(2/3), OWL showed significantly larger values than WR in the bone CSA of the upper arm and thigh and in the muscle CSA of the lower leg and thigh. However, lean CSA ratios of the upper extremities to the lower ones were significantly higher in WR than in OWL. Thus, the present results indicated that, compared to UM, OWL and WR had a greater lean tissue CSA in limbs, especially in the upper extremities, even when the difference in FFM was normalized. Moreover, the relative distribution of lean tissues in limbs differed between the two weight-categorized athletes in spite of there being no difference in FFM, which may be attributable to their own training regimens and/or competition style.